Coevolution between invasive and native plants driven by chemical competition and soil biota - Lankau, Richard A. (National Academy of Sciences, 2012)
Although reciprocal evolutionary responses between interacting species are a driving force behind the diversity of life, pairwise coevolution between plant competitors has received less attention than other species interactions and has been considered relatively less important in explaining ecological patterns. However, the success of species transported across biogeographic boundaries suggests a stronger role for evolutionary relationships in shaping plant interactions. Alliaria petiolata is a Eurasian species that has invaded North American forest understories, where it competes with native understory species in part by producing compounds that directly and indirectly slow the growth of competing species. Here I show that populations of A. petiolata from areas with a greater density of interspecific competitors invest more in a toxic allelochemical under common conditions. Furthermore, populations of a native competitor from areas with highly toxic invaders are more tolerant to competition from the invader, suggesting coevolutionary dynamics between the species. Field reciprocal transplants confirmed that native populations more tolerant to the invader had higher fitness when the invader was common, but these traits came at a cost when the invader was rare. Exotic species are often detrimentally dominant in their new range due to their evolutionary novelty; however, the development of new coevolutionary relationships may act to integrate exotic species into native communities.